The practice of everyday life - Certeau, Michel de, 1925-1986 (Berkeley : University of California Press, 1988)
"By exploring the public meanings of ingeniously defended private meanings the author describes the range of tactics available to the ordinary person for reclaiming his or her autonomy from the competing and all-pervasive forces of commerce, politics and culture"--publisher
I. A very ordinary culture -- II. Theories of the art of practice -- III. Spatial practices -- IV. Uses of language -- V. Ways of believing.
Translation of: Arts de faire.
"First paperback printing"--Verso of t.p.
Includes bibliographical references (p. 205-229).
Keywords: Social history; Civilization, Modern; Social ecology; Culture -- Philosophy